Keefektifan Limbah Tembakau sebagai Insektisida Nabati untuk Mengendalikan Hama Helopeltis sp. pada Kakao - Soekadar Wiryadiputra (Universitas Gadjah Mada, 2003)
The effectiveness of tobacco waste extract to control Helopeltis sp. on cocoa had been tested in laboratory and field conditions. Side effects of the extract on growth of cocoa flower and predatory insects of Helopeltis sp. had also been observed after field application. The results revealed that tobacco waste extract at 10.0% concentration in water was effective in suppressing the population of Helopeltis sp. both in laboratory and field trials, and it was not significantly different compared to cypermethrin 0.1% formulation and BPMC 0.2% formulation. Application of tobacco extract and insecticides did not result in negative effects on the growth of cocoa flower, nevertheless the tratmens affected the population of predatory insects of spiders and Reduviidae.